2001
DOI: 10.1074/jbc.m100515200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Interactions of Nucleotides at the Two Nucleotide Binding Domains of the Cystic Fibrosis Transmembrane Conductance Regulator

Abstract: After phosphorylation by protein kinase A, gating of the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel is regulated by the interaction of ATP with its nucleotide binding domains (NBDs). Models of this gating regulation have proposed that ATP hydrolysis at NBD1 and NBD2 may drive channel opening and closing, respectively (reviewed in Nagel, G. (1999) Biochim. Biophys. Acta 1461, 263-274). However, as yet there has been little biochemical confirmation of the predictions of these mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
126
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(146 citation statements)
references
References 29 publications
18
126
2
Order By: Relevance
“…4ab). This behavior, noted by others in studies of crude membranes [14,15], has not been reported for other ABC transporters [14,15,33] and may be a distinctive feature of CFTR.We also evaluated recovery of functional CFTR in a quantitative manner by comparing nucleotide trapping of CFTR in parallel with that of its well-characterized relative, Pgp, which had been expressed in Sf9 cells and purified and reconstituted using conditions optimized for its own recovery [33,[35][36][37]38] (Table I, Fig. 4c-e).…”
supporting
confidence: 54%
See 4 more Smart Citations
“…4ab). This behavior, noted by others in studies of crude membranes [14,15], has not been reported for other ABC transporters [14,15,33] and may be a distinctive feature of CFTR.We also evaluated recovery of functional CFTR in a quantitative manner by comparing nucleotide trapping of CFTR in parallel with that of its well-characterized relative, Pgp, which had been expressed in Sf9 cells and purified and reconstituted using conditions optimized for its own recovery [33,[35][36][37]38] (Table I, Fig. 4c-e).…”
supporting
confidence: 54%
“…4ab). This behavior, noted by others in studies of crude membranes [14,15], has not been reported for other ABC transporters [14,15,33] and may be a distinctive feature of CFTR.…”
Section: Nucleotide Processing By Purified and Reconstituted Cftrmentioning
confidence: 44%
See 3 more Smart Citations